Juridic Aspects of Startup Company in the Era of the Industrial Revolution and the Trend of Digitalization of Trade - Deli Bunga Saravistha; I Wayan Werasmana Sancaya (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2022)
Looking at the times and society's need for a modern form of technology-based business, it is interesting to discuss the topic of startup companies. Moreover, this form of business is now considered part of the trend of digitizing trade. In addition, e-commerce is a form of trend in the digital sector and today's economic sector. This research aims to examine the role of big data and the protection of personal data in startup companies and the legal relationship in it, and to examine the regulations regarding consumer protection for startup company users in Indonesia. This research was conducted using a normative research method, with a statutory approach and a case approach with descriptive and evaluative techniques. The results of this research revealed that the role of big data in the startup company business, among others, is to support business competition by using big data through innovation. Not only for startup companies, but for all current and future business ventures as well as for the government in relation to public services. The parties in the startup business other than the company itself, including consumers and the government as legal authorities. All of them have their respective important roles. Consumer protection is now the responsibility of OJK, in addition to the legal umbrella in the form of regulations issued by the OJK, regulations set by Bank Indonesia can also be used as the only central bank that has the capacity to determine monetary policy. In addition, it is also regulated in the ITE Law, which even though it is not sufficient to protect consumers, it can at least provide legitimacy for the protection of consumer data.